Effects of different biomass substrates on the adsorption of anti-inflammatory and estrogenic compound - Muhamad Alif Haikal, Abd Razak (2025)
The widespread of micropollutants such as pharmaceutical compound in WWTPs is now one of the biggest threats to global health. Pharmaceutical micropollutants, such as oestrogenic and anti-inflammatory compounds, can pollute water, posing serious health and environmental risks. This study examines how well various biomass substrates which are rice straw, corn cob and sugarcane waste to adsorb ibuprofen, an anti-inflammatory medication and an estrogenic compound (E2). The adsorption performance of these biomass substrates was assessed using zeolite as a baseline. By pyrolysing the biomass substrates, biochar was created. Its surface morphology, functional groups, and surface area properties were assessed using Brunauer-Emmett-Teller (BET) analysis, Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Batch studies were used to perform adsorption experiments at different pollutant concentrations (3 ppm, 5 ppm, and 10 ppm). Reverse-phased High-Performance Liquid Chromatography (RP-HPLC) was used to analyse the results. According to the results, sugarcane waste had the highest adsorption efficiency because of its superior surface area, pore volume, and functional group characteristics. All biomass substrates were found to effectively adsorp both ibuprofen and E2. Zeolite was a useful baseline even though its adsorption performance was lower. The study emphasises the potential of biochar made from agricultural waste as an economical and sustainable wastewater treatment method.